Early Local Activity in Temporal Areas Reflects Graded Content of Visual Perception - Tagliabue, Chiara F.; Mazzi, Chiara; Bagattini, Chiara; Savazzi, Silvia (Frontiers in Psychology, 2016)
In visual cognitive neuroscience the debate on consciousness is focused on two major topics: the search for the neural correlates of the different properties of visual awareness and the controversy on the graded versus dichotomous nature of visual conscious experience. The aim of this study is to search for the possible neural correlates of different grades of visual awareness investigating the Event Related Potentials (ERPs) to reduced contrast visual stimuli whose perceptual clarity was rated on the four-point Perceptual Awareness Scale (PAS). Results revealed a left centro-parietal negative deflection (Visual Awareness Negativity; VAN) peaking at 280-320 ms from stimulus onset, related to the perceptual content of the stimulus, followed by a bilateral positive deflection (Late Positivity; LP) peaking at 510-550 ms over almost all electrodes, reflecting post-perceptual processes performed on such content. Interestingly, the amplitude of both deflections gradually increased as a function of visual awareness. Moreover, the intracranial generators of the phenomenal content (VAN) were found to be located in the left temporal lobe. The present data thus seem to suggest 1) that visual conscious experience is characterized by a gradual increase of perceived clarity at both behavioral and neural level and 2) that the actual content of perceptual experiences emerges from early local activation in temporal areas, without the need of later widespread frontal engagement.